A new left economics : an economy with a social conscience - Von Brockdorff, Philip; Spiteri, Jonathan (Emerald points., 2024)
Exploring how the economy can develop and grow by upholding the social contract and giving social partners like trade unions the space and a key role in this new economy, A New Left Economics reviews the dominant neo-classical economic paradigm and provide insights into a new economic model by critically assessing the new left economics. Through revisiting Keynes and the relevance of Keynesian economic thinking today, von Brockdorff and Spiteri argue for going beyond GDP to a more social model based on welfare, reclaiming the word 'welfare' from neoclassical economics in the process. Incentivising the social economy enterprise model is also key to this new paradigm shift - the focus is never on curbing economic activity, but rather on making it work for more people to generate greater welfare. These could include cooperatives and employee-owned models, right through to certain circular economy models that promote social wellbeing. This is an accessible and intriguing text focusing on new left economics, revisiting and modernising Keynesian economic thinking to frame a basis for an economy with a strong social focus.